Creed & grievance : Muslim-Christian relations & conflict resolution in northern Nigeria - Mustapha, Abdul Raufu; Ehrhardt, David, 1982- (Woodbridge, Suffolk : James Currey, 2018)
In northern Nigeria, high levels of ethnic diversity have coincided with acute polarization between Muslims and Christians, increasingly fuelling violent conflict. The climate of insecurity threatens northern Nigeria's development, accentuates the inequalities between it and the rest of the country, and undermines the attempt to stabilize democracy in the country. Externally, fears have also been expressed that Islamist movements in northern Nigeria form part of a wider network constituting a threat to global peace and security. Refuting a "clash of civilizations" between Muslims and Christians, the authors of this new study highlight the multiplicity of Muslim and Christian groups contending for influence and relevance, and the doctrinal, political and historical drivers of conflict and violence between and within them. They analyse three of the most contentious issues: the conflicts in Jos; the Boko Haram insurgency; and the challenges of legal pluralism posed by the declaration of full Sharia law in 12 Muslim majority states. Finally, they suggest appropriate and effective policy responses at local, national and international levels, discussing the importance of informal institutions as avenues for peace-building and the complementarities between local and national dynamics in the search for peace. Abdul Raufu Mustapha is Associate Professor in African Politics, University of Oxford. David Ehrhardt is Assistant Professor of International Development at Leiden University College. Companion volume: Sects & Social Disorder: Muslim Identities & Conflict in Northern Nigeria edited by Abdul Raufu Mustapha, (James Currey 2014)
Nigerian society has long been perceived as divided along religious lines, between Muslims and Christians, but alongside this there is an equally important polarization within the Muslim population in beliefs, rituals and sectarian allegiance. This important book highlights the important issue of intra-Muslim pluralism and conflict in Nigeria. Conflicting interpretations of texts and contexts have led to fragmentation within northern Nigerian Islam, and different Islamic sects have often resorted to violence against each other in pursuit of 'the right path'. The doctrinal justification of violence was first perfected against other Muslim groups, before being extended to non-Muslims: conflict between Muslim groups therefore preceded the violence between Muslims and Christians. It will be impossible to manage the relationship between the latter, without addressing the schisms within the Muslim community itself.
Introduction : Religious encounters in northern Nigeria / Abdul Raufu Mustapha -- The Muslim majority in northern Nigeria : sects and trends / Philip Ostien -- The significant minority : Christians & Christianity in northern Nigeria / David Ehrhardt, Jibrin Ibrahim -- Historical contexts of Muslim-Christian encounters in northern Nigeria / Abdul Raufu Mustapha, David Ehrhardt, Rachael Diprose -- Challenges of legal pluralism : Sharia law & its aftermath / Abdul Raufu Mustapha, Aminu Gamawa -- Boko Haram, youth mobilization & jihadism / Marc-Antoine Pérouse de Montclos -- Complementary, competition & conflict : informal enterprise & religious conflict in northern Nigeria / Kate Meagher -- Jos : fear & violence in central Nigeria / Abdul Raufu Mustapha, Adam Higazi, Jimam Lar, Karel Chromy -- Rural insecurity on the Jos Plateau : livelihoods, land & cattle amid religious reform & violent conflict / Adam Higazi -- Jos : bottom-up & top-down approaches to peace building / Abdul Raufu Mustapha, Adam Higazi, Jimam Lar, Karel Chromy -- Conclusion : Diversity, religious pluralism & democracy / Abdul Raufu Mustapha, David Ehrhardt.
"First published in hardback and Africa-only paperback 2018"--Title page verso
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Islamic law -- Nigeria, Northern; Islamic courts -- Nigeria, Northern; Islam and politics -- Nigeria, Northern; Islam and state -- Nigeria, Northern; Democracy -- Nigeria, Northern -- Religious aspects; Islamic renewal -- Nigeria, Northern; Christianity -- Nigeria, Northern; Conflict management -- Nigeria, Northern; Christianity and other religions -- Islam; Nigeria -- Politics and government -- 2007-; Droit islamique -- Nigeria (Nord); Tribunaux islamiques -- Nigeria (Nord); Islam et État -- Nigeria (Nord); Renouveau islamique -- Nigeria (Nord); Christianisme -- Nigeria (Nord); Gestion des conflits -- Nigeria (Nord); Christianisme -- Relations -- Islam; Nigeria -- Politique et gouvernement -- 2007-; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity; Conflict management; Democracy -- Religious aspects; Interfaith relations; Islam; Islam and politics; Islam and state; Islamic courts; Islamic law; Islamic renewal; Politics and government; Nigeria; Northern Nigeria; Since 2007